Perlindungan Hukum Pekerja Kontrak dalam Perspektif Asas Proporsionalitas dalam Hukum Ketenagakerjaan - Atmari Atmari; Sudjai Sudjai (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The development of employment relations in Indonesia shows an increasing tendency toward flexibility through the use of Fixed-Term Employment Agreements (PKWT) or contract workers. On the one hand, this policy supports business needs in creating efficiency and labor market adaptability; on the other hand, it raises serious concerns regarding legal protection for workers who are in a weaker bargaining position. This study aims to analyze the regulation of legal protection for contract workers within the Indonesian labor law system, examine its conformity with the principle of proportionality, and formulate a more equitable legal reconstruction. This research employs a normative legal research method (doctrinal legal research) using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively through prescriptive legal reasoning. The findings indicate that the regulation of PKWT in Indonesia is still predominantly oriented toward economic flexibility, and therefore has not fully reflected the principle of balance embedded in proportionality. This condition results in the weak bargaining position of contract workers and suboptimal legal protection. Accordingly, this study proposes a legal reconstruction based on the principle of proportionality through the limitation of PKWT, strengthening workers’ rights, and improving labor supervision mechanisms. The implications of this study are expected to contribute theoretically to the development of a more equitable labor law system and provide policy direction for legislators in strengthening worker protection in Indonesia.